Rationality in Medieval Literature – The Roots of Modernity in the Middle Ages? - Classen, Albrecht (International Journal of Culture and History, 2024)
This study attempts to push the boundaries of our historical-intellectual concept regarding the origin and development of rationality as a modus vivendi not only since the eighteenth century, but already as an intellectual force in the Middle Ages, primarily reflected in literary works. While traditional courtly narratives reveal only tentative elements of rational thought patterns and forms of behavior, as soon as we turn to thirteenth-century romances and short verse mæren, do we recognize the emergence of rationality already in the pre-modern world. Rationality is here not identified as a comprehensive philosophical system pursued by the various poets; instead, it is perceived as a pragmatic approach to everyday situations in the lives of the various protagonists who commonly face dilemmatic situations and must apply ratiocination in order to come to terms with specific challenges, considering and balancing out contrastive options to limit harm to themselves and to make the best out of the conditions confronting them.